Inrush and airblast barricades for caving mines - Thomas, A; Joughin, W; Jakubec, J (MassMin 2024: 9th International Conference & Exhibition on Mass Mining, 2024)
Major hazards inherent to cave mining include the potential for inrush and airblast. Evaluating and managing the risks associated needs to be part of mine planning, operations, and closure. Barricading underground openings is a common mitigation measure and barricade types can range from simple muck piles up to fully engineered reinforced concrete structures. A critical component of the design process is defining the possible driving forces that the barricade will need to resist. This is challenging due to the complexity of underground mine networks and uncertainties around where, when, and how these hazardous events might occur. The authors discuss an event scenario assessment which was used to evaluate and select the events to form the basis of design.